Pengenalan Ragam Keanekaragaman Hayati dalam Cerita Rakyat Kalimantan Timur - Norma Atika Sari (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
The focus of this research is an analysis of the forms of recognition of biodiversity that are displayed in the folklore of East Borneo. Biodiversity in question includes the diversity of genes, species, and ecosystems. The folk tales studied were stories that had been transcribed into a book entitled East Borneo Folklore (1981) published by Balai Pustaka. There are 20 titles of stories in it with the background of the life of the people of East Kalimantan and 3 stories were selected as research samples. The method used is descriptive qualitative. Data was obtained by using reading and note-taking techniques. The approach chosen in this research is the study of children's literature and eco-sastra. The purpose of this study is to describe the diversity of genes, species and ecosystems typical of East Borneo in folklore so that they can be used as learning media for children to recognize, love, and protect the natural environment of East Borneo. The results of the study found the diversity of flora and fauna typical of East Borneo. There are not many forms of exploration of genetic diversity in the research sample. Data on species diversity was found in the research sample, namely various types of fish endemic to East Borneo: biawan fish, jelawat fish, haruan, porpoise fish. It also explained the myth of the formation of the dolphin fish and the Borneo rhinoceros. The river ecosystem dominates daily life which is clearly visible in all of the existing folklore. Through cheerful people, children will recognize the culture of their homeland through the following stages: (1) introduction, (2) love, (3) habituation, and (4) preserving.